2021
DOI: 10.1021/acsptsci.0c00200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of P-Glycoprotein Does Not Increase the Efficacy of Proteasome Inhibitors in Multiple Myeloma Cells

Abstract: The aim of this study is to determine whether manipulation of the drug transporter Pglycoprotein improves the efficacy of proteasome inhibitors in multiple myeloma cells. Pglycoprotein is a well-known drug transporter that is associated with chemotherapy resistance in a number of cancers but its role in modulating the efficacy of proteasome inhibitors in multiple myeloma is not well understood. Research has shown that the second generation proteasome inhibitor carfilzomib is a substrate of P-glycoprotein and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 48 publications
(100 reference statements)
0
18
0
Order By: Relevance
“…Controversy also surrounds the expression level of CD38 on MM plasma cells and responses to anti-CD38 monoclonal antibodies such as daratumumab, which are efficacious even when cell surface expression is low [4]. Similarly, mechanisms of resistance to proteasome inhibitors are still not well understood, with mutations in proteasome subunits or expression of multi-drug resistance transporters evident in only a minority of cases and of questionable involvement [4,[92][93][94]. Recently, the poor prognostic impact of desmoglein-2 on the malignant plasma cells of newly diagnosed MM patients has been demonstrated with efforts underway to elucidate its biological role in MM and to develop targeted therapeutics [95].…”
Section: Proteomicsmentioning
confidence: 99%
“…Controversy also surrounds the expression level of CD38 on MM plasma cells and responses to anti-CD38 monoclonal antibodies such as daratumumab, which are efficacious even when cell surface expression is low [4]. Similarly, mechanisms of resistance to proteasome inhibitors are still not well understood, with mutations in proteasome subunits or expression of multi-drug resistance transporters evident in only a minority of cases and of questionable involvement [4,[92][93][94]. Recently, the poor prognostic impact of desmoglein-2 on the malignant plasma cells of newly diagnosed MM patients has been demonstrated with efforts underway to elucidate its biological role in MM and to develop targeted therapeutics [95].…”
Section: Proteomicsmentioning
confidence: 99%
“…However, it’s unclear if the upregulation of ABCB1 in these cells results from increased GCS. Further, it was reported that the GCS inhibitor eliglustat did not induce ABCB1 protein on the cell surface in the KMS-18 MM cell line ( 199 ). Fu et al.…”
Section: Sphingolipids As Mediators Of Drug-resistance In MMmentioning
confidence: 99%
“…There is controversy about whether bortezomib is a ABCB1 substrate, but carfilzomib is, and therefore MM cells with increased ABCB1 are more carfilzomib resistant. However, in many MM cell lines, ABCB1 expression is very low on the cell surface, and the specific ABCB1 inhibitor tariquidar did not enhance the sensitivity to either bortezomib or carfilzomib, so the relevance to MM biology and proteasome inhibitor resistance is unclear ( 199 ). A few studies suggest that ABCG2 in MM cells may contribute to intrinsic drug resistance, which is increased when the cells are exposed to ABCG2 substrates such as doxorubicin or topotecan ( 200 , 201 ).…”
Section: Sphingolipids As Mediators Of Drug-resistance In MMmentioning
confidence: 99%
“…It is generally agreed that bortezomib is a poor substrate of P-gp. ,− Similar to lenalidomide, however, there is conflict in the literature regarding this drug; some researchers have shown that genetic or pharmacological inhibition of P-gp increases MM and other cancer cell sensitivity to bortezomib (Table ). ,, …”
Section: Drug Transportersmentioning
confidence: 99%